Essential role of CREB family proteins during Xenopus embryogenesis - Lutz, Beat; Schmid, Wolfgang; Niehrs, Christof; Schütz, Günther (Mechanisms of development, 1999)
The leucine zipper transcription factors cAMP response element binding protein (CREB), cAMP response element modulatory protein (CREM) and activating transcription factor 1 (ATF1) bind to the cAMP response element (CRE) with the palindromic consensus sequence TGACGTCA. Their transcriptional activities are dependent on serine phosphorylation induced by various extracellular signals such as hormones, growth factors and neurotransmitters. Here we show that CREB is the predominant CRE-binding protein in Xenopus embryos and that it plays an essential role during early development. The importance of CREB for morphogenetic processes was assessed by injection of RNA encoding a dominant-negative form of CREB that is fused to a truncated progesterone receptor ligand binding domain. In this fusion protein, a dominant-negative function can be induced by application of the synthetic steroid RU486 at given developmental stages. The inhibition of CREB at blastula and early gastrula stages leads to severe posterior defects of the embryos reflected by strong spina bifida, whereas the inhibition of CREB at the beginning of neurulation resulted in stunted embryos with microcephaly. In these embryos, initial induction of neural and mesodermal tissues is not dependent on CREB function, as genes such as Otx2, Krox20, Shh and MyoD are still expressed in injected embryos. But the expression domains of Otx2 and MyoD were found to be distorted reflecting the abnormal development in both neural and somitic derivatives. In summary, our data show that CREB is essential during several developmental stages of Xenopus embryogenesis.
Gesehen am 18.02.2019